Про функціональні моделі комутативних систем операторів у просторах Л. де Бранжа - Сировацький, Вiталiй; Syrovatskyi, Vitaliy (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Для комутативної системи лінійних обмежених операторів Т 1, Т 2, які діють в Гільбертовому просторі Н, і не один з операторів Т 1, Т 2 не є стискуванням, розглянуто окремий випадок функціональної моделі, яка буду-ється в просторі Л. де Бранжа для круга. ; The commutative system of the linear limited operators T 1, T 2 which operate in Hilbert space H, and not one of operators T 1, T 2 is compression, is studied. Functional model for given system of operators is build in space of Louis De Branges for a circle. Special case is studied in model when on vectors (1, −1) T and (1, 1) T operators N and Ñ turns to zero, but for operators Г and they are eigenvectors. Also the meaning of the equations of the special case is studied
About Functional Models of Commutative Systems of Operators in Spaces of Louis De Branges
Keywords: функціональна модель; простор Л. де Бранжа; functional model; space of Louis De Branges